Poskolonial dan Krisis Maksulinitas Dars dalam Wina 60: Analisis Babha dan Connell: Ambivalensi, Peniruan, dan Maskulinitas yang Terpinggirkan: Pembacaan Bhabha-Connell terhadap Dars di Wina 60 - Saryfa Amanda; Abdul Muntaqim Al Anshory (Language Development Center, 2025)
Background: the cultural clash between East and West when Dars visited Vienna in the 1960s. Purpose: Analyze the postcolonial form and crisis of masculinity experienced by Dars in Yusuf Idris' novel Vienna. Method: Using a qualitative descriptive research design Regarding the text of Vienna 60, by Yusuf Idris with textual analysis using Miles & Huberman. The primary data was the text of novel Vienna 60 by Yusuf Idris. The research population was the entire text of the novel, and the sample consisted of sentences containing elements of postcolonialism (Bhabha) and the crisis of masculinity (Connell). The instruments were developed by the researcher himself, and the data collection technique was note-taking and reading. The data analysis technique was data reduction, data presentation, and verification. Results and Discussion: The findings show that Dars experiences an identity and masculinity crisis. Ambivalence is evident when he admires Western culture but also feels alienated. Mimicry is seen when he tries to imitate the language used by Westerners. The potential for hybridity occurs in his encounters with Western women. Dars experiences a masculinity crisis related to his race and origins in the East. Therefore, Dars exhibits ambivalence, failed mimicry, and marginalized/subordinate masculinity. This research contributes by adding gender issue analysis of the character. Conclusions and Implications: Dars experiences cultural incompatibility, which causes him to experience a crisis of masculinity. This illustrates how migration between the West and the East not only experiences alienation but also gender issues. This study expands the postcolonial discourse in modern Arabic literature by integrating gender analysis through Connell's lens. Therefore, it is hoped that further research will deepen postcolonial studies, especially gender in literary works.